(untitled) (Equilibrium: Jurnal Pendidikan, 2025)
This study aims to understand how female massage therapists working independently in Samarinda City construct their identities, interpret their bodies, and negotiate social stigma associated with their profession. The therapists in this research are migrants from various regions who previously worked in traditional massage parlors or spas but now choose to work independently without formal institutional affiliation. A qualitative approach using ethnographic methods within the framework of socio-cultural anthropology was employed to explore the subjective experiences and cultural practices of the informants. Data were collected through participant observation, semi structured interviews, and documentation of daily activities. Informants were purposively selected based on criteria including age (20 - 45 years), migration background, and experience working independently as therapists. Data analysis was conducted thematically through transcription, open coding, theme identification, and contextual interpretation. The findings reveal that independent female massage therapists develop cultural agency through flexible work choices, management of private spaces as practice locations, and identity narrative adjustments to mitigate social stigma. The body is positioned both as a source of livelihood and a symbolic field strategically negotiated within a socially ambiguous space. Keywords : women; massage therapists; body; social stigma